Celastrol attenuates the invasion and migration and augments the anticancer effects of bortezomib in a xenograft mouse model of multiple myeloma - Shanmugam, M.; Ahn, K.; Lee, J.; Kannaiyan, R.; Mustafa, N.; Manu, K.; Siveen, K.; Sethi, G.; Chng, W.; Kumar, Alan Prem (2018)
© 2018 Shanmugam, Ahn, Lee, Kannaiyan, Mustafa, Manu, Siveen, Sethi, Chng and Kumar. Several lines of evidence have demonstrated that deregulated activation of NF-?B plays a pivotal role in the initiation and progression of a variety of cancers including multiple myeloma (MM). Therefore, novel molecules that can effectively suppress deregulated NF-?B upregulation can potentially reduce MM growth. In this study, the effect of celastrol (CSL) on patient derived CD138+ MM cell proliferation, apoptosis, cell invasion, and migration was investigated. In addition, we studied whether CSL can potentiate the apoptotic effect of bortezomib, a proteasome inhibitor in MM cells and in a xenograft mouse model. We found that CSL significantly reduced cell proliferation and enhanced apoptosis when used in combination with bortezomib and upregulated caspase-3 in these cells. CSL also inhibited invasion and migration of MM cells through the suppression of constitutive NF-?B activation and expression of downstream gene products such as CXCR4 and MMP-9. Moreover, CSL when administered either alone or in combination with bortezomib inhibited MM tumor growth and decreased serum IL-6 and TNF-a levels. Overall, our results suggest that CSL can abrogate MM growth both in vitro and in vivo and may serve as a useful pharmacological agent for the treatment of myeloma and other hematological malignancies.